Water quality monitoring of two main rivers during construction phase of highway Ketereh to Kok Lanas, Kelantan / Muhammad Faiz Roslan - Muhammad Faiz, Roslan (2022)
River as source of freshwater to human and other living creatures. Construction activities are intensifying in Malaysia that revolve around river. River water quality are important during the construction phase to prevent pollution. This study was conducted to determine the water quality based on Water Quality Index (WQI) by Department of Environmental Malaysia of two main rivers during construction phase of highway Ketereh to Kok Lanas, Kelantan. The factors affected the water quality was identified during this construction phase especially the activity near to the river bank and river crossing, also any other external factor that affected river water quality. Control measures implemented by the contractor was determine to prevent the river pollution. Parameters in WQI taken into condition which are pH Value @ 25°C, Biochemical Oxygen Demand BOD-5 test @ 20° C (mg/I), Chemical Oxygen Demand (COD) (mg/I), Total Suspended Solids (mg/I), Ammoniacal Nitrogen : (mg/I), and Dissolved Oxygen : (mg/I), included E.coli. Lubok Sendong River located along the alignment of this highway project are considered as slightly polluted from year 2018 until 2020 within Class III and clean in the year of 2021 with the Class II. Meanwhile for Mahang River average condition within the Class III and considered as slightly polluted from year 2018 until 2021. The contractor of this highway project take extensive erosion and sedimentation control measures to prevent the both of river pollution by conducted Erosion and Sedimentation Control Measures approved by the local authority and designed by professional engineer. The maintenance of the control measures play important roles during this construction phase to ensure the effectiveness of sediment and soil loss into the rivers.